KEPEDULIAN TERHADAP LINGKUNGAN HIDUP MELALUI PENGAJARAN GEOGRAFI SEJARAH DI LPTK - Soebijantoro, Soebijantoro (Jurnal Pendidikan, 2012)
Ecosystem has been one target of the UNOs millenium development goals. The decision is sited because the safety of the ecosystem is regarded to be critical around the development of science and technology of 20th century which result in not only well-being but also disaster for human mankind, pertaining to complicated problems. The role of technology has shifted along the way with the development of human history, from the support system to power which determines the cosietal behaviour and interaction.Technology is always coined with science, since technlogy is the embodiment of the science. Hence, technology will only develop in the assistance of the cultural behaviour which contributesÂ  strategic advantage for human being. The development of technology inavitably requires the deep structure of ethics, moral and commitment to establish the basis of a nations culture. The most responsible institution to nurture such values is educational institution.One of the objectives of teaching historical geography is to nurture students awareness against the significance of ecosystem, thorugh the historical cultural and geographical approaches, around and within human life and living.Key words: Ecosystem, Historical Geography